Community on Mission in a World Wounded by Poverty: A Call to Solidarity, Vulnerability and Liberation - Churu, Beatrice W. E.; Getui, Mary N. (Ecclesial Futures, 2021)
This paper explores two faces of poverty—the poverty of the wretched of the earth, and that of the lords of poverty. Both are bereft of dignity and humanity. Illustrations from the African context are given. Christian community on mission in a world choking on poverty is highlighted as modelled on the Jesus event, the humanness of God—a paradox of vulnerability bringing breath and life. Ubuntu, the African disposition to choose growth into fuller humanity, is proposed to aid a meaningful African Christian engagement with the various forms of poverty. Experiences of an encounter between the two faces of poverty at St Martin’s Catholic Social Apostolate in Nyahururu demonstrate how the Christ experience of openness to humanness—solidarity and vulnerability— can turn poverty into liberating grace.